Thermoregulation in babies immediately after birth. - Smales, O R (1978)
The fall in body temperature that occurs in babies soon after birth is influenced by the baby's weight and its environmental conditions. The rate of oxygen consumption 1 1/2 hours after birth was unrelated to body temperature and only slightly raised, indicating a limited thermogenic capacity. A radiant heater effectively prevented cooling in babies kept with their mothers in the delivery room. Washing soon after birth caused a significant cooling. Healthy term babies were found to have a limited thermogenic response to a cool environment over the first 12 hour of life and efforts to limit heat losses should be concentrated on this period.